The Effect of a Role-Playing Counseling Program on Developing Social Belonging among University Students (Journal of the College of Basic Education, 2025)
The research aimed to determine the effect of a role-playing counseling program on developing social belonging among university students. This was achieved by verifying the following null hypotheses:- There were no statistically significant differences at the 0.05 level between the scores of the experimental group in the pre- and post-tests on the social belonging scale.- There were no statistically significant differences at the 0.05 level between the scores of the control group in the pre- and post-tests on the social belonging scale.- There were no statistically significant differences at the 0.05 level between the scores of the experimental and control groups in the post-test on the social belonging scale.The researcher adopted the Social Belonging Scale prepared by (Attia, 2021), which consisted of (40) items and four domains, with (10) items in each domain. The apparent validity of the scale was determined by presenting it to a number of arbitrators. Construct validity was previously verified, given that the scale was adopted. For reliability, the test-retest method and Cronbach's alpha coefficient were used for internal consistency. The researcher used a role-playing method to develop social belonging. The number of sessions was (6), the duration of each session was (45) minutes, with two sessions per week. The program continued for (3) weeks. To verify the validity of this program, it was presented to a group of experts specializing in psychological counseling, who confirmed its validity in developing social belonging.The researcher reached the following results:- There are statistically significant differences at the (0.05) level between the scores of the experimental group in the pre- and post-tests on the Social Belonging Scale.There were no statistically significant differences at the 0.05 level between the scores of the control group in the pre- and post-tests on the social belonging scale.- There were statistically significant differences at the 0.05 level between the scores of the experimental and control groups in the post-test on the social belonging scale, in favor of the experimental group.In light of these results, the researcher made a number of recommendations and proposals.